PENGARUH STOCK OPNAME DAN PENGENDALIAN INTERNAL TERHADAP KEPUASAN KONSUMEN DENGAN KETERSEDIAAN KOPI SEBAGAI VARIABEL INTERVENING DI KOFFIEHUIS PEMATANGSIANTAR - Betriks Sinaga (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study aims to analyze the effect of stock opname and internal control on customer satisfaction with coffee availability as an intervening variable at Koffiehuis Pematangsiantar. This quantitative research employed questionnaires distributed to 132 respondents and was analyzed using multiple regression. The results show that stock opname and internal control significantly affect customer satisfaction, both directly and through coffee availability. The coffee availability variable plays a role in strengthening the relationship between the independent variables and customer satisfaction. These findings highlight the importance of effective inventory management and internal control systems to maintain product availability, enhance customer satisfaction, and foster customer loyalty.